Households’ Fuel Wood Dependence, REDD+ and Gender Coping Strategies: An Empirical Review and Policy Implication in the Northern Region of Ghana - Mohammed, Jamal; Osei-Fosu, Anthony Kofi; Yusif, Hadrat (International Journal of Environment, 2017)
This paper reviewed existing literature on fuel wood dependence, REDD+ and gender coping strategies. Out of 180 sets of empirical studies in this domain, twenty five (25) were considered to have a bearing on our topic. The review showed that REDD+ policy in the Northern Region has not provided for REDD+ finance to curb the possible negative effects of the implementation of the programme. It is recommended that there should be a clear cut policy on REDD+ finance for those who depend on the forest. It is also recommended that there should enough public education for communities’ acceptance and integration.INTERNATIONAL JOURNAL OF ENVIRONMENTVolume-5, Issue-4, Sep-Nov 2016, page: 12-31